Evaluation of hybrid nanoparticles to oxygenated fuel with ethanol and n- butanol on combustion behavior. (15th July 2023) - Atelge, M.R.; Arslan, Esenay; Kahraman, Nafiz; Ünalan, Sebahattin
Graphical abstract: Highlights: Pm of OFm increased ∼ 2.9% compared to D under the full load. BTEs of Dm and OFm were noticed to be 5.5% and 3% higher than D. CO, and UHC of OFm compared to D dropped by 49.1%, and 54.2% OFm showed better performances and emission characteristics. Abstract: The internal combustion engine type is widely used in diesel engines due to its energy efficiency. However, the use of conventional diesel has negative effects on human health and the environment. In an effort to find a more sustainable fuel option with less harmful emissions, the focus has shifted towards investigating the effects of hybrid nano additives, which are a combination of nonmetallic (graphene nanoplate) and metal oxide (TiO2 ), on conventional diesel (D) and oxygenated fuels (OF). The engine test was conducted at 4 different loading cases with increments of 25% from 25% to 100% at a constant speed of 1500 rpm. The results showed that the modified fuels had superior combustion behaviors, such as peak in-cylinder pressure, combustion duration, and ignition delay, compared to conventional diesel and oxygenated fuels. The peak pressures in the cylinder of modified diesel (Dm ) and modified oxygenated fuel (OFm ) under full load increased by 2% and 2.9%, respectively, compared to conventional diesel (D). Additionally, the brake thermal efficiencies (BTEs) of Dm and OFm were found to be 5.5% and 3% higher than D under the same test conditions. In terms of emission analysis, the modified fuels demonstrated superiority over the conventional diesel and oxygenated fuels. During full load conditions, the CO, UHC, and NO emissions of OFm compared to D dropped by 49.1%, 54.2%, and 4%, respectively. The study results indicate that the use of a hybrid fuel additive consisting of nonmetallic (graphene nanoplate) and metal oxide (TiO2 ) can significantly reduce harmful emissions and improve engine performance.